A educação de jovens e adultos: desafios de uma proposta de educação inclusiva: perfil do aluno - Lima, Fabiana de Oliveira [UNESP]; Silva, Nilson Rogério da [UNESP] (My University, 2014)
The inclusion of students with disabilities in youth and adult education is still new and there is little literature on the issue, which makes it both nationally relevant, and timely in the context of the construction of inclusive schools for all. The present study aimed to characterize the profile of the student of Youth and Adult Education in a medium size city of São Paulo, between the years 2011 and 2013. For the study documentary analysis was carried out using the Student Registration System of the State of São Paulo (PRODESP) for the study. A roadmap for the characterization of students was used, as a research instrument. It was possible to obtain data regarding the total enrolment per year, number of students with disabilities, types of disabilities, gender and age. Youth and Adult Education’s search for people with disabilities is increasing and accordingly, we observe that the target audience of YAE today has changed, including people with disabilities, indicating the need to consider development of teaching practices in line with the needs and demands of new YAE students.

A inclusão de alunos com deficiência na EJA é um tema ainda novo e há pouca literatura sobre o assunto, o que o torna, além de relevante nacionalmente, oportuno no contexto de construção de escolas inclusivas para todos. O presente trabalho teve o objetivo de caracterizar o perfil do aluno da Educação de Jovens e Adultos em um município de médio porte do estado de São Paulo, entre os anos de 2011 e 2013. Para o estudo, procedeu-se à análise de documentos, utilizando-se o Sistema de Cadastro de Alunos do estado de São Paulo (PRODESP). O instrumento utilizado foi um roteiro de caracterização dos alunos. Foi possível levantar dados referentes ao total de matrículas por ano, número de alunos com deficiência, tipos de deficiência, gênero e faixa etária. A procura pela EJA por pessoas com deficiência vem aumentando e, nesse sentido, observa-se que o público-alvo da EJA está mudando, incluindo a pessoa com deficiência, o que indica que é preciso se pensar em desenvolvimento de práticas pedagógicas em consonância com as necessidades e as demandas dos novos alunos da EJA.
Youth and adult education and the challenges of a proposal for inclusive education: student profile
Keywords: Educação de Jovens e Adultos - EJA; educação inclusiva